2007
DOI: 10.1021/tx7002867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligonucleotides Containing the N2-Deoxyguanosine Adduct of the Dietary Carcinogen 2-Amino-3-methylimidazo[4,5-f]quinoline

Abstract: Abstract2-Amino-3-methylimidazo [4,5-f]quinoline (IQ) is a highly mutagenic heterocyclic amine formed in all cooked meats. IQ has been found to be a potent inducer of frameshift mutations in bacteria and carcinogenic in laboratory animals. Upon metabolic activation, IQ forms covalent adducts at the C8-and N 2 -positions of deoxyguanosine with a relative ratio of up to ~4:1. We have previously incorporated the major dGuo-C8-IQ adduct into oligonucleotides through the corresponding phosphoramidite reagent. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 88 publications
2
14
1
Order By: Relevance
“…The synthesis of this adduct into oligodeoxynucleotides (67) has allowed the conformation of the N 2 -dG-IQ adduct at the G 3 position of this sequence to be determined. This is a hot spot for two-base frameshift deletions in bacterial mutagenesis assays (68–71,73,74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of this adduct into oligodeoxynucleotides (67) has allowed the conformation of the N 2 -dG-IQ adduct at the G 3 position of this sequence to be determined. This is a hot spot for two-base frameshift deletions in bacterial mutagenesis assays (68–71,73,74).…”
Section: Discussionmentioning
confidence: 99%
“…The N 2 -dG-IQ-adducted oligodeoxynucleotide 5′-d(CTCGGCXCCATC)-3′ was synthesized as described ( 67 ). The complement strand 5′-d(GATGGCGCCGAG)-3′ was synthesized by Midland Certified Reagents Co. (Midland, TX, USA) and purified by anion exchange chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The N 2 -dG-IQ adduct was incorporated into 5′-d(CTC X GCGCCATC)-3′ using automated solid-phase synthesis. 63 It was located at position X 4 , corresponding to position G 1 in the Nar I sequence (Chart 1 ). The modified oligodeoxynucleotide was purified by C18 reverse-phase HPLC and characterized by MALDI-TOF mass spectrometry in negative ion mode (modified strand m / z obsvd, 3779; calcd, 3778; complementary strand m / z obsvd, 3712; calcd, 3711).…”
Section: Resultsmentioning
confidence: 99%
“…26 It may play a significant role in cancer etiology. 18 , 19 Polymerase bypass studies conducted in vitro have revealed that the consequences of replication past the N 2 -dG-IQ adduct differ when the lesion was incorporated 63 , 72 at position G 1 vs G 3 of the Nar I restriction endonuclease sequence, 5′-d(G 1 G 2 CG 3 CC)-3′. 66 71 Two-base deletions were produced by hpol η when the N 2 -dG-IQ adduct was located at the G 3 position, but when this lesion was located at the G 1 position, error-free incorporation of dCTP occurred but further replication stalled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation